2007
DOI: 10.1097/jcp.0b013e31803308e1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Study Design on the Results of Continuation Studies of Antidepressants

Abstract: Antidepressant continuation studies have used 2 different designs. In the placebo substitution design, all patients are initially treated with active medication in an open-label fashion, and then treatment responders are randomized to continue with medication or switch to placebo in a double-blind manner. In the extension design, patients are randomized to a double-blind placebo-controlled acute study at the outset, and responders to active treatment and placebo are continued on the treatment to which they ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…At week 12, participants are aware that they may be randomized to placebo, which may decrease their expectancy of continued improvement (i.e., decreased placebo effect) or increase their expectation of worsening (i.e., increased nocebo effect). Such expectancy effects in continuation studies of antidepressants have been found by Zimmerman et al (2007), who compared relapse rates to antidepressants and placebo in studies using a placebo-substitution (i.e., open acute treatment with active medication followed by randomization to continued medication or placebo) vs. extension designs (i.e., responders to double-blind acute treatment with medication or placebo continue taking what they responded to in continuation phase) (27). Overall relapse rates were reported to be lower in extension studies, likely due to a greater expectation of continued positive response in these studies where patients are aware they will continue taking the agent that made them better.…”
Section: Discussionmentioning
confidence: 83%
“…At week 12, participants are aware that they may be randomized to placebo, which may decrease their expectancy of continued improvement (i.e., decreased placebo effect) or increase their expectation of worsening (i.e., increased nocebo effect). Such expectancy effects in continuation studies of antidepressants have been found by Zimmerman et al (2007), who compared relapse rates to antidepressants and placebo in studies using a placebo-substitution (i.e., open acute treatment with active medication followed by randomization to continued medication or placebo) vs. extension designs (i.e., responders to double-blind acute treatment with medication or placebo continue taking what they responded to in continuation phase) (27). Overall relapse rates were reported to be lower in extension studies, likely due to a greater expectation of continued positive response in these studies where patients are aware they will continue taking the agent that made them better.…”
Section: Discussionmentioning
confidence: 83%
“…Antidepressant drugs, psychotherapy, and their combination can be effective in preventing relapse and recurrence (Viguera et al 1998;Paykel et al 1999;Kupfer and Frank 2001;Paykel 2001;Kennedy et al 2002;Lépine et al 2004;Blier et al 2007), although study design can influence the magnitude of the benefit observed (Zimmerman et al 2007b). A systematic review of 31 randomised studies involving 4410 participants concluded that continuation of a treatment with antidepressant drugs reduced the odds of relapse by 70% relative to placebo; average relapse-rates were 18% on active antidepressant therapy and 41% on placebo, respectively (Geddes et al 2003).…”
Section: Rationale For Long-term Treatmentmentioning
confidence: 94%
“…These comparative trials were extension trials and did not re-randomize patients to continuation or maintenance treatment, but rather gave patients the option to continue on with their blinded acute-phase treatment. This trial design has been shown to produce overall lower relapse rates, but larger differences between active treatment and placebo than placebo substitution trials that randomizes participants at the time of successful acute-or continuation-phase completion (42). For this reason, we limited our meta-analyses to placebo substitution trials.…”
Section: Discussionmentioning
confidence: 99%